Synthesis method and application of layered NH4V4O10 adsorbing material for selectively adsorbing 228Ra and 224Ra

By preparing layered NH4V4O10 adsorbent material and utilizing its high selectivity for Ra(II), the problems of large separation devices, large material consumption, and high cost in the existing technology were solved, and efficient separation of 228Ra and 224Ra was achieved, which helps to solve the problem of 212Pb raw material supply.

CN122035947APending Publication Date: 2026-05-15NANHUA UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610448435.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-07
Publication Date
2026-05-15

AI Technical Summary

Technical Problem

In existing technologies, conventional separation materials are more selective for Th(IV) than for Ra(II), resulting in large separation devices, high material consumption, and high separation costs, making it difficult to efficiently extract 228Ra and 224Ra from 232Th.

Method used

Layered NH4V4O10 adsorbent material was prepared by hydrothermal synthesis. Taking advantage of its significantly higher selectivity for Ra(II) than Th(IV), and combining pH adjustment, adsorption, washing and desorption steps, selective separation of 228Ra and 224Ra was achieved.

Benefits of technology

It significantly reduced the size of the separation unit and the amount of materials used, lowered the separation cost, achieved efficient extraction of 228Ra and 224Ra, and solved the problem of insufficient supply of 212Pb raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122035947A_ABST
    Figure CN122035947A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method and application of a layered NH4V4O10 adsorbing material for selectively adsorbing 228Ra and 224Ra. LiOH is used as a mineralizing agent, and layered NH4V4O10 is prepared through a hydrothermal synthesis method; the NH4V4O10 adsorbent with a layered structure is obtained through material design and screening, the interlayer spacing of the NH4V4O10 adsorbent reaches the angstrom level, and the NH4V4O10 adsorbent can show excellent selectivity to Ra (II) in a Th (IV) / Ra (II) binary medium through the ion size recognition effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radioactive element separation technology, specifically to a method for selective adsorption and separation of radioactive elements from thorium salt solutions. 228 Ra、 224 Layered materials of Ra and their application methods are suitable for the separation and purification of radioactive isotopes in nuclear chemical engineering, especially for medical radioactive isotopes. 212 We provide technical support for the supply of raw materials for Pb. Background Technology

[0002] 212 Pb is a promising medical radioactive isotope, but its resources are extremely scarce, mainly due to a severe shortage of its generator nucleus and raw materials. 228 Ra、 224 Ra is the preparation 212 Pb is a key raw material, and this type of raw material can be obtained from 232 Obtained from the Th decay chain, therefore from a large number of 232 High-efficiency separation and extraction of Th 228 Ra、 224 Ra is a fundamental solution. 212 The key to the Pb scarcity problem.

[0003] In the prior art, the closest Th / Ra separation scheme to this invention utilizes traditional ion exchange resins or extraction resins, achieving separation through adsorption or chromatography based on the difference in their affinity for Th(IV) and Ra(II). These materials include cation exchange resins with sulfonic acid groups, anion exchange resins with quaternary ammonium groups, and extraction resins loaded with extractants. However, because Th(IV) has a higher charge density than Ra(II) and is more readily coordinated with common ligands, conventional separation materials generally preferentially bind to Th(IV), exhibiting poor selectivity for Ra(II).

[0004] The essence of the above method is to achieve the separation and extraction of Ra by removing a large amount of Th, while natural Ra... 232 The Th / Ra mass ratio in the Th decay chain is as high as nine orders of magnitude or more. The high Th / Ra ratio leads to the drawbacks of this type of method in practical applications, such as large separation equipment, large material consumption, and high separation cost, which limits its practical value. Summary of the Invention

[0005] To address the core deficiency of conventional adsorption materials in existing technologies where the selectivity for Th(IV) is higher than that for Ra(II), this invention aims to develop a novel Th / Ra separation material with significantly higher selectivity for Ra(II) than for Th(IV), and to establish a corresponding separation method, fundamentally solving the problems of large separation devices, large material consumption, and high separation costs in existing technologies.

[0006] This invention provides a method for selective adsorption 228 Ra、 224 Layered NH4V4O of Ra 10 The method for synthesizing adsorbent materials involves using LiOH as a mineralizing agent and preparing layered NH4V4O through a hydrothermal synthesis method. 10 .

[0007] In a second aspect, the present invention provides a method for selective adsorption. 228 Ra、 224 Layered NH4V4O of Ra 10 The method for synthesizing adsorbent materials includes the following steps: Dissolve NH4VO3 and an equimolar amount of LiOH in distilled water and stir until clear; Add dipropylamine, with a molar ratio of NH4VO3 to dipropylamine of 1:0.5, and adjust the pH of the solution to 4.0 by adding acetic acid dropwise. Continue stirring with a magnetic stirrer at 600 r / min for 30 min to obtain the precursor solution. The precursor solution was transferred to a 30 mL polytetrafluoroethylene-lined high-pressure reactor with a filling degree of 66.6%, and the temperature was programmed to rise to 180 °C at 10 °C / min and reacted at a constant temperature for 72 h. After natural cooling, the product was collected, washed by centrifugation, and dried under vacuum at 80°C to obtain a green powdery layered NH4V4O. 10 Adsorbent materials.

[0008] Preferably, the prepared NH4V4O 10 The adsorbent material adsorbs 1.2 mmol / g of the Ra-simulated element Ba, but only 0.12 mmol / g of Th.

[0009] Thirdly, the present invention provides a method for selective adsorption and separation of thorium nitrate solution. 228 Ra、 224 The Ra method, via layered NH4V4O 10 As an adsorbent, it undergoes sequential steps of solution pH adjustment, adsorption, washing, and desorption to achieve [the desired effect]. 228 Ra、 224 Selective separation of Ra.

[0010] Preferably, the solution pH is adjusted by dissolving thorium nitrate in dilute nitric acid solution to adjust the system pH to 2-4.

[0011] Preferably, the adsorption step involves adding layered NH4V4O to a pH-adjusted thorium nitrate solution. 10 Add the adsorbent material and stir continuously for 2-3 hours until adsorption equilibrium is reached.

[0012] Preferably, the washing step involves using dilute nitric acid with a pH of 2-3 to wash the NH4V4O after adsorption equilibrium. 10 Wash the adsorbent material 2-3 times.

[0013] Preferably, the desorption step involves using a 1.0M NH4Cl solution to desorb the washed NH4V4O 10 The adsorbent material is rinsed to achieve 228 Ra、 224 Desorption of Ra.

[0014] Preferably, after rinsing 228 Ra、 224 The desorption recovery rate of Ra is not less than 90%, and the Th concentration in the desorbed solution is only 0.2% of that in the original solution.

[0015] Fourthly, the present invention provides a layered NH4V4O 10 Adsorbent material selectively adsorbs thorium salt solution 228 Ra、 224 In the application of Ra, the thorium salt solution is a thorium nitrate solution, and the pH of the solution is adjusted to 2-4; when Th in the thorium nitrate solution... 4+ When the concentration is in the range of 0.001~0.1mol / L, layered NH4V4O 10 right 228 Ra、 224 The adsorption efficiency of Ra remained at 96%~98%.

[0016] III. Beneficial Effects This invention, through material design and screening, yields NH4V4O with a layered structure. 10 The adsorbent, with interlayer spacing reaching the angstrom level, exhibits excellent selectivity for Ra(II) in Th(IV) / Ra(II) binary media through the ion size recognition effect.

[0017] Compared with existing technologies, this invention achieves a first-ever "polar reversal" of the adsorption selectivity of adsorbent materials for Th(IV) / Ra(II), shifting from the traditional "massive removal of Th" to "selective adsorption of trace amounts of Ra." Even in a 0.1M thorium salt solution, near-complete adsorption of Ra can be achieved, and only a small amount of NH4Cl solution is needed to complete the Ra elution. This technology significantly reduces the scale of separation equipment, material usage, and separation costs, providing a new direction for the development of high-efficiency separation technologies. 228 Ra、 224 The efficient extraction of Ra provides a practical solution, thereby helping to solve the problem. 212 The problem of raw material supply for Pb. Attached Figure Description

[0018] Figure 1 : 232A schematic diagram of the Th decay chain is shown. 228 Ra、 224 The origin of Ra in the decay chain; Figure 2 NH4V4O 10 The XRD diffraction pattern confirmed that the synthesized product was the target layered material; Figure 3 NH4V4O 10 N2 adsorption-desorption curves; Figure 4 The type of mineralizer affects NH4V4O 10 The effect of separating Ba (a simulated element of Ra) / Th properties demonstrates the superiority of LiOH as a mineralizer; Figure 5 NH4V4O 10 The adsorption capacity of Ba and Th under different pH conditions was compared to show the suitable pH range; Figure 6 The desorption efficiency of different desorbents for Ba and Th was compared, showing that 1.0MNH4Cl had the best desorption effect. Figure 7 Th concentration on NH4V4O 10 The effect of Ra adsorption efficiency is shown, demonstrating the material's anti-interference performance; Figure 8 The comparison of the separation performance of various adsorbents for Ba and Th demonstrates the unique selectivity of the material of this invention. Detailed Implementation

[0019] The technical solutions in the embodiments will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection.

[0020] The technical solution of this invention includes layered NH4V4O 10 Synthesis of adsorbent materials and selective adsorption and separation of thorium nitrate solutions based on these materials. 228 Ra、 224 The Ra method is as follows: (a) Layered NH4V4O 10 Synthesis methods of adsorption materials It is prepared by hydrothermal synthesis using LiOH as a mineralizing agent, and the steps are as follows: Dissolve 0.0100 mol (1.1698 g) NH4VO3 and 0.0100 mol (0.42 g) mineralizing agent LiOH in 10 mL of distilled water and stir on a magnetic stirrer at 600 r / min until clear; Add 0.6856 mL of dipropylamine (approximately 0.005 mol, calculated based on the measured density of the reagent). At this point, the molar ratio of NH4VO3 to dipropylamine is 1:0.5. While stirring, add acetic acid dropwise to adjust the pH of the solution to 4.0. Continue stirring at 600 r / min for 30 min to obtain the precursor solution. The precursor solution was transferred to a 30 mL polytetrafluoroethylene-lined high-pressure reactor with a filling degree of 66.6%. After sealing, the temperature was programmed to rise to 180 °C at a heating rate of 10 °C / min and reacted at a constant temperature for 72 h.

[0021] After natural cooling, the product was collected, washed several times by centrifugation with distilled water, and dried in a vacuum drying oven at 80℃ to obtain a green powdery layered NH4V4O. 10 Adsorbent materials; XRD analysis confirmed that the synthesized product was the target product, and its BET specific surface area was determined by ultra-low temperature N2 adsorption-desorption.

[0022] (ii) Selective adsorption separation from thorium nitrate solution 228 Ra、 224 Ra method The overall steps are as follows: Dissolve thorium nitrate in dilute nitric acid solution and adjust the pH to 2-4; Take a certain amount of layered NH4V4O 10 Add the adsorbent material to the thorium nitrate solution with the pH adjusted above, and stir continuously for 2-3 hours until adsorption equilibrium is reached; Solid-liquid separation was performed by filtration. The filtered thorium solution was collected and properly disposed of, and the adsorbent was stored for future use. Wash the adsorbent 2-3 times with dilute nitric acid at pH 2-3; The adsorbent was eluted with a 1.0 M NH4Cl solution, and the adsorbed... 228 Ra、 224 Ra is washed down, achieving separation with a separation efficiency of over 90%.

[0023] The present invention will be further described in detail below with reference to embodiments and comparative examples, but the present invention is not limited to the following embodiments.

[0024] Example 1 According to the above layered NH4V4O 10 Synthesis method of adsorbent material to prepare layered NH4V4O 10 The adsorbent material was confirmed by XRD analysis to be the target material (e.g., ...). Figure 2 As shown); the peaks (001), (002), and (003) show a reciprocal ratio of 1:2:3, confirming a layered structure; the interlayer spacing of the (001) crystal plane is calculated to be 9.57 Å using the Bragg equation.

[0025] Layered NH4V4O prepared according to the above synthesis method 10 The adsorbent material, confirmed by N2 adsorption-desorption testing, has a BET specific surface area of ​​approximately 7.50 m²·g⁻¹. Its N2 adsorption-desorption isotherm is as follows: Figure 3 As shown, no hysteresis loops were observed, indicating that the material has a relatively small number of micropores and mesopores.

[0026] Example 2 Prepare a working solution containing 1.0 mMTh and 1.0 mMBa (simulated elements of Ra) with pH=3. Take 20 mg of the adsorbent material synthesized in Example 1 and mix it with 25 mL of the working solution. After sealing, place it in a 25°C constant temperature water bath shaker and shake at 120 rpm for 2 h. Solid-liquid separation was performed using a 0.45 μm microporous membrane. The filtrate was diluted and analyzed by ICP-AES. The results showed that ( Figure 4 Layered NH4V4O 10 The adsorption capacity for Ba reached 1.2 mmol / g, while the adsorption capacity for Th was only 0.12 mmol / g, demonstrating its excellent adsorption selectivity for Ra-like elements.

[0027] Example 3 Configure multiple 1.0mMTh 4+ With 1.0mMBa 2+ The mixed solutions were adjusted to pH values ​​of 2.3, 2.5, 3.0, 3.3, and 3.9, respectively. Take several 40mL glass bottles, add 20mg of adsorbent material to each, then add 20mL of mixed solution with different pH values, seal and then shake at 120rpm for 2h in a 25℃ constant temperature water bath shaker. After solid-liquid separation, the filtrate was analyzed by ICP-AES. The results showed that within the pH range of 2.3 to 3.9, the adsorbent material exhibited higher adsorption selectivity for Ba and weaker adsorption capacity for Th (e.g., ...). Figure 5 (As shown).

[0028] Example 4 Add 20 mg of adsorbent material and 20 mL of pH 2.5 solution containing 1 mmol / L Th to a 25 mL beaker. 4+ With 1 mmol / L Ba 2+ The mixed solution was stirred and adsorbed at room temperature for 2 hours, and then allowed to stand for 30 minutes. Take 10 mL of the supernatant for later use, add 10 mL of 1.0 M NH4Cl solution to the remaining system, restore the total volume to 20 mL, and stir at room temperature for 2 h to desorb; Analysis of the filtrate after solid-liquid separation showed that 1.0M NH4Cl had a desorption efficiency of up to 95% for Ba, but virtually no desorption for Th, indicating good separation performance (e.g., ...). Figure 6 (As shown).

[0029] Example 5 Configure Th 4+ Take 4 mL of each of the solutions with concentrations of 0.001, 0.01, 0.025, 0.05, and 0.1 mol / L, and 1 mL of a solution with an activity of 216 Bq / mL. 226 Mix Ra standard solutions; The characteristic peak region at 186.4 keV was measured using a high-purity germanium gamma spectrometer. 226 Ra daughter body 214 Initial counts of Pb were performed, and the live time was measured for 2 hours. Add 5 mg of adsorbent to each sample vial, stir at 600 rpm at room temperature for 2 hours for adsorption, and measure the concentration of adsorbent in the filtrate after solid-liquid separation. 226 Ra count rate, calculate adsorption efficiency; The results showed that as the Th concentration increased from 0.001 M to 0.1 M, the adsorption material's effect on... 226 The adsorption efficiency of Ra remained consistently between 96% and 98%, while the Th concentration had almost no effect on the adsorption efficiency, demonstrating excellent anti-interference performance (e.g., Figure 7 (As shown).

[0030] Example 6 Take the load in Example 4 226 The Ra adsorbent material was washed 2-3 times with dilute nitric acid at pH 2.5. The load was slowly washed with 5 mL of 1.0 M NH4Cl. 226 The adsorbent material for Ra was used, and the process was repeated three times. Gamma spectroscopy was used to analyze the filtrate. 226 Ra total activity, results showed: 226 The Ra recovery rate was approximately 92%, and the Th concentration in the filtrate was only 0.2% of that in the original solution, achieving... 226 Efficient separation of Ra from Th salt solutions.

[0031] Comparative Example 1 The procedure was the same as in Example 1, except that the mineralizer LiOH was replaced with an equimolar amount of NaOH or KOH, or no mineralizer was added. The results showed that: Without the addition of mineralizers, the adsorbent material has good effect on Th. 4+ and Ba 2+ The adsorption properties are similar, but there is insufficient selectivity. When the mineralizing agent is NaOH, for Ba 2+ It exhibits good selectivity, but the adsorption capacity is significantly reduced. When the mineralizing agent is KOH, it affects Th 4+ Selectivity higher than Ba 2+ None of these methods can be used for the separation of trace amounts of Ra in large quantities of Th (e.g. Figure 4 (As shown).

[0032] Comparative Example 2 The procedure was the same as in Example 2, except that the pH of the mixed solution was adjusted to 1.0, 1.7, and 2.0. The results showed that when the pH was below 2.0, the adsorption capacity of the adsorbent material for Ba decreased significantly, and the adsorption capacity for Th also decreased. 4+ Higher selectivity, unable to achieve target separation (e.g.) Figure 5 (As shown).

[0033] Comparative Example 3 The procedure was the same as in Example 3, except that the desorbent was replaced with 0.5M ammonium citrate, 0.5 mol / L EDTA-2Na, 0.001 mol / L EDTA, or 0.005 mol / L EDTA. The results showed that these desorbents were less effective at desorbing Ba than 1.0M NH4Cl, and they also significantly desorbed Th (e.g., ...). Figure 6 (As shown).

[0034] Comparative Example 4 Prepare a solution containing 1.0 mM Th 4+ and 1.0mM Ba 2+ The mixed solution has a pH adjusted to 2.5.

[0035] Take several clean 40mL glass bottles and add 20mg of different adsorbent materials to each, including: NH4V4O synthesized in this invention. 10 Commercial cation exchange resin (model: Purolite C100EFG, abbreviated as C100EFG, purchased from Purolite), HDEHP-loaded extraction resin (HDEHP / SiO2-P, prepared in the laboratory), P507-loaded extraction resin (P507 / SiO2-P, prepared in the laboratory), TRPO-loaded extraction resin (TRPO / SiO2-P, prepared in the laboratory), TBP-loaded extraction resin (TBP / SiO2-P, prepared in the laboratory), commercial anion exchange resin (model IRA900, purchased from Shanghai Maclean Biochemical Reagent Co., Ltd.), silicon-based cation exchange resin (named A1, prepared in the laboratory), and MnS2-Sb2S3 composite adsorbent (prepared in the laboratory).

[0036] Add 20 mL of a mixed solution containing Th and Ba to a glass bottle, then seal it and place it in a 25°C constant temperature water bath shaker for adsorption at 140 rpm for 2 h.

[0037] Immediately after the adsorption time point, solid-liquid separation was performed using a 0.45 μm microporous membrane, and the filtrate was analyzed using ICP-AES. The adsorption efficiency of each material for Th and Ba was calculated based on the changes in the concentrations of Th and Ba in the solution before and after adsorption.

[0038] The results show that, except for the NH4V4O of this invention 10 In addition, other materials preferentially adsorb Th or do not adsorb either, making it impossible to achieve selective separation of trace amounts of Ra from a large amount of Th (e.g., Figure 8 (As shown).

[0039] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for selective adsorption 228 Ra、 224 Layered NH4V4O of Ra 10 The method for synthesizing adsorbent materials is characterized by, Layered NH4V4O was prepared by hydrothermal synthesis using LiOH as a mineralizing agent. 10 .

2. The selective adsorption according to claim 1 228 Ra、 224 Layered NH4V4O of Ra 10 The method for synthesizing adsorbent materials is characterized by, Includes the following steps: Dissolve NH4VO3 and an equimolar amount of LiOH in distilled water and stir until clear; Add dipropylamine, with a molar ratio of NH4VO3 to dipropylamine of 1:0.5, and adjust the pH of the solution to 4.0 by adding acetic acid dropwise. Continue stirring with a magnetic stirrer at 600 r / min for 30 min to obtain the precursor solution. The precursor solution was transferred to a 30 mL polytetrafluoroethylene-lined high-pressure reactor with a filling degree of 66.6%, and the temperature was programmed to rise to 180 °C at 10 °C / min and reacted at a constant temperature for 72 h. After natural cooling, the product was collected, washed by centrifugation, and dried under vacuum at 80°C to obtain a green powdery layered NH4V4O. 10 Adsorbent materials.

3. The selective adsorption according to claim 1 228 Ra、 224 Layered NH4V4O of Ra 10 The method for synthesizing adsorbent materials is characterized by, The prepared NH4V4O 10 The adsorbent material adsorbs 1.2 mmol / g of the Ra-simulated element Ba, but only 0.12 mmol / g of Th.

4. A method for selective adsorption and separation of thorium nitrate solutions 228 Ra、 224 The Ra method is characterized by, Through layered NH4V4O 10 As an adsorbent, it undergoes sequential steps of solution pH adjustment, adsorption, washing, and desorption to achieve [the desired effect]. 228 Ra、 224 Selective separation of Ra.

5. The selective adsorption and separation of thorium nitrate solution according to claim 4 228 Ra、 224 The Ra method is characterized by, The solution pH was adjusted by dissolving thorium nitrate in dilute nitric acid solution to adjust the system pH to 2-4.

6. The selective adsorption separation from thorium nitrate solution according to claim 4 228 Ra、 224 The Ra method is characterized by, The adsorption step involves adding layered NH4V4O to a thorium nitrate solution with adjusted pH. 10 Add the adsorbent material and stir continuously for 2-3 hours until adsorption equilibrium is reached.

7. The selective adsorption separation from thorium nitrate solution according to claim 4 228 Ra、 224 The Ra method is characterized by, The washing step involves using dilute nitric acid (pH 2-3) to wash the NH4V4O after adsorption equilibrium. 10 Wash the adsorbent material 2-3 times.

8. The selective adsorption and separation of thorium nitrate solution according to claim 4 228 Ra、 224 The Ra method is characterized by, The desorption step involves using a 1.0M NH4Cl solution to desorb the washed NH4V4O 10 The adsorbent material is rinsed to achieve 228 Ra、 224 Desorption of Ra.

9. The selective adsorption separation from thorium nitrate solution according to claim 8 228 Ra、 224 The Ra method is characterized by, After rinsing 228 Ra、 224 The desorption recovery rate of Ra is not less than 90%, and the Th concentration in the desorbed solution is only 0.2% of that in the original solution.

10. A layered NH4V4O 10 Adsorbent material selectively adsorbs thorium salt solution 228 Ra、 224 The application of Ra is characterized by, The thorium salt solution is a thorium nitrate solution, and the pH of the solution is adjusted to 2-4; when the thorium nitrate solution contains Th... 4+ When the concentration is in the range of 0.001~0.1mol / L, layered NH4V4O 10 right 228 Ra、 224 The adsorption efficiency of Ra remained at 96%~98%.